Prevalence and predictors of disability for Māori 24 months after injury. (28th March 2017) - Wyeth, Emma H.; Samaranayaka, Ari; Davie, Gabrielle; Derrett, Sarah
Abstract: Objective: To investigate post‐injury disability prevalence and identify pre‐injury and injury‐related predictors 24 months post‐injury among Māori Prospective Outcomes of Injury Study participants. Methods: Participants were recruited from New Zealand's no‐fault injury insurer. Pre‐injury and injury‐related characteristic information was obtained from participants at three and 24 months post‐injury. The World Health Organization Disability Assessment Schedule was used to measure disability. Multivariable models were developed to estimate relative risks of post‐injury disability. Results: Of 2, 856 participants, 566 were Māori. Analyses were restricted to 374 Māori with pre‐injury and 24‐month post‐injury disability data available. Pre‐injury, 9% reported disability compared to 19% 24 months post‐injury. Strong predictors of increased risk of disability 24 months post‐injury were having ≥2 chronic conditions pre‐injury and having trouble accessing healthcare services after injury. Hospitalisation for injury and having inadequate pre‐injury household income were other predictors. Conclusions: Māori experience considerable disability 24 months post‐injury. Pre‐injury socio‐demographic, health and psychosocial, and injury‐related characteristics independently predict post‐injury disability and provide focus for future research and interventions to improve Māori post‐injury outcomes. Implications for public health: Despite having had access to services, injured Māori experienced considerable long‐term disability. Pre‐injury and injury‐related factors predict long‐term disability and should be the focus to reduce the post‐injury disability burden for Māori.